Sensitivity of normal mouse marrow and RIF-1 tumour to hyperthermia combined with cyclophosphamide or BCNU: a lack of therapeutic gain. - Honess, D. J. (Nature Publishing Group, 1982)
The effect of simultaneous whole-body heat (45 min 41 degrees C) on cyclophosphamide (CTX) and BCNU toxicity to normal mouse marrow stem cells and to the RIF-1 tumour in C3H/He mice has been studied. Marrow stem-cell survival was assayed by the spleen-colony technique at both 2 and 24 h after treatment, and also by following peripheral WBC count during the weeks after treatment. Heat potentiation of CTX toxicity to marrow stem cells was similar at both times and 24 h after treatment heat was dose-modifying with a DMF of 2.0. The heat potentiation of BCNU toxicity to stem cells was much greater at 24 h than at 2 h, and at 24 h had a DMF of 2.1. Peripheral WBC counts supported the results from 24 h assay for both drugs. RIF-1 tumour response was assayed by clonogenic cell survival measured 24 h after treatment, and by growth delay. For clonogenic tumour-cell survival after CTX, heated and unheated curves were parallel at doses above 75 mg/kg, yielding DMFs varying between 1.9 and 1.4 according to dose. DMFs for BCNU were also dose-dependent, lying between 2.0 and 1.6, the RIF-1 tumour being much less sensitive to BCNU than to CTX. Growth-delay data agreed with clonogenic cell survival. Therapeutic ratios for the combination of heat with CTX or BCNU fell in the range 0.91--0.69, according to dose, i.e. no gain or even therapeutic loss under the conditions of this study.